2023
DOI: 10.1186/s40478-023-01607-9
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of DNA methylation to the (dys)function of oligodendroglia in neurodegeneration

Abstract: Neurodegenerative diseases encompass a heterogeneous group of conditions characterised by the progressive degeneration of the structure and function of the central or peripheral nervous systems. The pathogenic mechanisms underlying these diseases are not fully understood. However, a central feature consists of regional aggregation of proteins in the brain, such as the accumulation of β-amyloid plaques in Alzheimer’s disease (AD), inclusions of hyperphosphorylated microtubule-binding tau in AD and other tauopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Emerging research has shed light on the dynamic nature of DNA methylation in neurodegenerative disorders and its impact on disease progression [ 121 ]. For instance, studies have shown altered DNA methylation patterns in genes associated with amyloid-beta processing and tau phosphorylation in Alzheimer’s disease (AD) [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging research has shed light on the dynamic nature of DNA methylation in neurodegenerative disorders and its impact on disease progression [ 121 ]. For instance, studies have shown altered DNA methylation patterns in genes associated with amyloid-beta processing and tau phosphorylation in Alzheimer’s disease (AD) [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a comprehensive understanding of the specific epigenetic changes and their functional consequences in different neurodegenerative disorders remains an area of active research. Unraveling the complexities of epigenetic regulation in these diseases may lead to identifying biomarkers and novel therapeutic targets, ultimately providing hope for more effective treatments in the future [ 121 , 140 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is an important epigenetic mechanism that mainly occurs at CpG sites and regulates gene transcription by remodeling chromatin conformation [ 55 ]. Extensive research has revealed widespread alterations in DNA methylation patterns in the brain tissues of AD patients [ 56 ]. These differentially methylated genes are involved in AD-related pathological processes, including neurodevelopment, neuroplasticity, inflammatory immune responses, calcium homeostasis, cholesterol metabolism, and myelin metabolism.…”
Section: Dna Methylation and Pathogenesis Of Admentioning
confidence: 99%
“…Additionally, genetic variants in MOBP have been associated with PSP risk [10, 25, 54]. Oligodendrocytes are one of the major cell types in the white matter (up to 75%) that contribute to the formation of myelin sheaths and have been time and again shown to play important roles in several neurodegenerative disease mechanisms [17, 46]. Moreover, DNA methylation patterns suggest accelerated epigenetic ageing in these cells suggesting a vulnerability of oligodendrocytes to ageing [42, 43], which might, at least in part, be contributed by changes in DNA methylation.…”
Section: Introductionmentioning
confidence: 99%